Differential effects of d-sotalol on subendocardial Purkinje myocytes isolated from normal or 10 to 14 days postinfarction canine hearts: role of extracellular potassium concentration - Marschang, Harald; Schöls, Wolfgang; Karolyi, Laszlo; Beyer, Thorsten; Kübler, Wolfgang; Brachmann, Johannes (Journal of cardiovascular pharmacology, 1998)
Electrophysiologic properties of surviving Purkinje cardiomyocytes in the late postmyocardial-infarction phase are not well established. By using standard microelectrode techniques, we evaluated the effects of the class III agent d-sotalol on action potential parameters of single Purkinje cardiomyocytes isolated from normal canine hearts or those 10-14 days after infarction. Measurements were obtained at 2.5, 3.5, and 6 mM extracellular potassium concentrations. Action-potential parameters recorded at baseline did not differ significantly between normal and infarct-surviving Purkinje cardiomyocytes. At 3.5 and 6 mM extracellular potassium concentrations, surviving Purkinje cells appeared to be more sensitive to the effects of d-sotalol than normal Purkinje cells. In contrast, at 2.5 mM extracellular potassium concentration, the differential responses of normal and infarctsurviving Purkinje cells to d-sotalol was abolished. Reverse rate dependence was more prominent in normal than in postinfarction Purkinje cells, independent of the extracellular potassium concentration studied. The previously described enhanced sensitivity of subacutely infarcted tissue to class III agents seems to persist on a cellular level 10-14 days after myocardial infarction, even after full normalization of baseline action-potential parameters. Differential membrane-regulation mechanisms, dependent on the extracellular potassium concentrations, may account for the increased susceptibility to antiarrhythmia agents in the late postinfarction phase.